2014
DOI: 10.1103/physrevb.89.184414
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion magnetic structure of an ordered FePt monolayer deposited onPt(111)

Abstract: The effect of the Dzyaloshinsky-Moriya interaction on the magnetic structure of an ordered FePt monolayer deposited on Pt (111) surface has been investigated. In the ground state, the pronounced anisotropic geometry of the FePt layer with alternating Fe and Pt chains gives rise to a helimagnetic structure with a strong difference in the helicity period along the chains and perpendicular to them. In the presence of an external magnetic field, the region of stable Skyrmion magnetic structures in the B − T phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(73 reference statements)
1
14
0
6
Order By: Relevance
“…This leads in the case of MnGe to a significant compensation of all contributions. For a more realistic description of the experimental situation at finite temperature, involving in particular non-collinear spin texture, Monte Carlo simulations based on atomistic spin models might be important [31]. …”
Section: Resultsmentioning
confidence: 99%
“…This leads in the case of MnGe to a significant compensation of all contributions. For a more realistic description of the experimental situation at finite temperature, involving in particular non-collinear spin texture, Monte Carlo simulations based on atomistic spin models might be important [31]. …”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15]27,36 In Fig. 2 the magnitudes of the DM vectors between the Fe atoms are shown as a function of the inter-atomic distance for all considered layer relaxations.…”
Section: 35mentioning
confidence: 99%
“…Since this initial discovery there has been tremendous growth in the field as an increasing number of materials have been found that can support a skyrmion phase [3][4][5][6][7][8][9][10] . There are also numerous proposals on how to stabilize skyrmion states by utilizing different materials properties or bilayers [11][12][13][14] . Direct imaging of skyrmions with Lorentz microscopy [3][4][5]7,10 and other techniques 8,15,16 show that the skyrmions form a triangular lattice and have particle-like properties similar to vortices in type-II superconductors 17 .…”
Section: Introductionmentioning
confidence: 99%